Dataset on the RETRO-BMC cruise onboard the R/V Hespérides, April 2017, Brazil-Malvinas Confluence - Orúe Echevarría, Dorleta (2020)
This dataset, gathered during the RETRO-BMC cruise, reports multiple-scale measurements at the Confluence of the Brazil and Malvinas Currents. The cruise was carried out between 8 and 28 April 2017 onboard R/V Hespérides, departing from Ushuaia and arriving to Santos. Along its track, the vessel recorded near-surface temperature and salinity, as well as the horizontal flow from 20 m down to about 800 m. A total of 33 hydrographic stations were completed in a region off the Patagonian Shelf, within 41.2°S–35.9°S and out to 53.0°W. At each station, a multiparametric probe and velocity sensors were deployed inside the frame of a rosette used to collect water samples at selected depths; these samples were later used for several water analyses, including inorganic nutrient concentrations. Microstructure measurements were carried out in 11 of these hydrographic stations. In addition, two high-resolution three-dimensional surveys were conducted with an instrumented undulating vehicle between 40.6°S–39.0°S and 55.6°W–53.8°W. Lastly, eight high-frequency vertical profilers were deployed in the region and five position-transmitting drifters were launched. These data allow the description of the Confluence from the regional scale to the microscale, and provide a view of the variability of the frontal region on time scales from days to weeks.